Oral squamous cell carcinoma (OSCC)-derived exosomal MiR-221 targets and regulates phosphoinositide-3-kinase regulatory subunit 1 (PIK3R1) to promote human umbilical vein endothelial cells migration and tube formation. Issue 1 (1st January 2021) - He, Shuqi; Zhang, Wu; Li, Xian; Wang, Junjie; Chen, Xufeng; Chen, Yu; Lai, Renfa
ABSTRACT: Oral squamous cell carcinoma (OSCC) is the most common tumor of the oral cavity. Studies have shown that exosomal miRNAs from cancer cells play an important role in mediating the cellular environment. The objective was to investigate the effect of OSCC-derived exosomes microRNA-221 (miR-221) in OSCC. We used quantitative real-time PCR (qRT-PCR) and western blotting to determine PIK3R1 and miR-221 expressions in OSCC tissue or peripheral blood serum. Exosomes of OSCC cell line CAL27 were extracted and characterized. Exosomal miR-221 expression was detected by qRT-PCR. Dual-luciferase was performed to validate the targeted regulatory relationship of miR-221 on PIK3R1. Transwell and tube formation assay were applied to detect the effect of OSCC-derived exosomal miR-221 on HUVEC migration and angiogenesis. qRT-PCR confirmed that PIK3R1 expression was downregulated in OSCC tissue and cell line, while miR-221 expression was upregulated. miR-221 expression in OSCC cell line-derived exosome elevated. miR-221 could target and negatively regulate PIK3R1 expression. In addition, OSCC-derived miR-221 could promote HUVEC migration and angiogenesis. In conclusion, OSCC-derived exosomal miR-221 could target and negatively regulate PIK3R1 expression, as well as promote vascular endothelial cell migration and angiogenesis. GRAPHICAL ABSTRACT: uf0001